2021
DOI: 10.3390/pharmaceutics13091501
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Multifunctional Thymol-Loaded Biodegradable Nanoparticles for Topical Acne Treatment

Abstract: The present work is focused on the development of novel surface-functionalized poly(lactic-co-glycolic acid) nanoparticles loaded with thymol (TH-NPs) for topical administration enhancing thymol anti-inflammatory, antioxidant and wound healing activities against acne. TH-NPs were prepared by solvent evaporation method using different surface functionalization strategies and obtaining suitable physicochemical parameters and a good short-term stability at 4 °C. Moreover, TH-NPs skin penetration and antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…As can be observed in Figure 3, Lico-A PLGA NPs were stable at 4 °C and 25 °C even after 3 months of storage. However, at 38 °C, the formulations were clearly unstable obtaining variations of the BS superior to 10% [55,56]. These results correlate with other obtained by previous authors using PLGA nanocarriers [43].…”
Section: Short-term Stability Of Licochalcone-a Plga Npssupporting
confidence: 89%
See 1 more Smart Citation
“…As can be observed in Figure 3, Lico-A PLGA NPs were stable at 4 °C and 25 °C even after 3 months of storage. However, at 38 °C, the formulations were clearly unstable obtaining variations of the BS superior to 10% [55,56]. These results correlate with other obtained by previous authors using PLGA nanocarriers [43].…”
Section: Short-term Stability Of Licochalcone-a Plga Npssupporting
confidence: 89%
“…Although all of the formulations were very similar, as can be observed in Table 4, Moreover, release profiles of all the formulations were very similar, being able to release Lico-A within the first 24 h after their application. In addition, this release from biodegradable nanocarriers is usually governed by a diffusion process since it is much faster than the matrix degradation [55]. Release data were fitted to a hyperbola equation [60][61][62].…”
Section: Drug Release Of Licochalcone-a Functionalized Nanoparticlesmentioning
confidence: 99%
“…To examine in vitro the cytotoxicity of GBE‐PEC NS against HaCaT cells at varying concentrations from 1 to 3 mg/ml, an MTT assay was carried out with PBS serving as a control. The cell line was chosen since it has been utilized as a substitute for human keratinocytes in numerous cytotoxicity investigations of percutaneous drug formulations 52,53 . In comparison to the PBS control, GBE‐PEC NS displayed >85% cell viability over the entire concentration range studied, the findings (Figure 10) revealed that cytotoxicity was dose‐dependent and minimal under application‐relevant conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The short-term stability of the PF-NLCs-F127 hydrogel (Figure 6) did not detect signs of destabilization over 60 days at 25 • C since the BS profile revealed variations of less than ±10%, indicating that the formulation was stable [34,35].…”
Section: Discussionmentioning
confidence: 99%